Bromatological characteristics and ruminal digestibility of grain corn hybrids with different vitreousness in silage maturity - Evandrei Santos Rossi; Marcos Ventura Faria; Marcelo Cruz Mendes; Mikael Neumann; André Gabriel; Murilo Viotto Del Conte (Acta Scientiarum. Agronomy, 2016)
The aim of this research was to evaluate vitreousness in commercial corn hybrids with flint and dent grains and to study the effect of this characteristic on agronomic behavior, nutritional value, and ruminal degradability of grains harvested in silage maturity. Twelve commercial corn hybrids were evaluated. They were divided in two groups (six with flint grains and six with dent grains). The experiments were conducted in two municipalities represented by Guarapuava and Laranjeiras do Sul, both in Paraná State. The harvest for the grain quality analysis was performed at ¾ of the milk line stage in the grain. The following characteristics were evaluated: grain yield, grain yield in silage maturity, vitreousness, ruminal digestibility of grain, neutral detergent fiber, acid detergent fiber and crude protein. The grains in the group of dent hybrids exhibited better degradability associated with lower vitreousness than the group of flint hybrids. The group of dent hybrids exhibited better ruminal digestibility of the grains associated with lower vitreousness versus the group of flint hybrids. There is a negative correlation between vitreousness and the digestibility of the grain; thus, vitreousness can be a criterion for selecting genotypes for forage production.